Legal Problems Regarding the Implementation of the Obligation to Read the Notary Deed - Hendy Hendariyadi; Jawade Hafidz; Soegianto Soegianto (Jurnal Akta, 2020)
Reading the deed is an obligation in every authentic deed is made, the reading of the deed by a notary is part of the verlijden or the inauguration of the reading and signing of the deed in question. If the reading of this deed is related to the making of an authentic deed which is part of perfect proof, it is clear that making a notary deed requires the real presence and physical position of the parties concerned. The purpose of this research is to analyze the Notary Public is obliged to read out the deed made based on Act No. 2 of 2014 concerning the Position of Notary Public, To analyze the legal problems of reading deeds made by the Notary, To analyze the legal consequences of deeds that are not read by a Notary based on Act No. 2 of 2014 concerning the Position of a Notary Public. The method used in this research is the method used in this research is juridical empirical, namely an approach based on applicable law and based on reality in practice. The juridical approach is used to analyze regulations that are related to the Notary Law, while the empirical approach is used to analyze the obligations of notaries in reading deeds which are seen as community behavior that has a pattern in community life that always interacts and relates to social aspects. namely an approach based on applicable law and based on reality in practice. The juridical approach is used to analyze regulations that are related to the Notary Law, while the empirical approach is used to analyze the obligations of notaries in reading deeds which are seen as community behavior that has a pattern in community life that always interacts and relates to social aspects. namely an approach based on applicable law and based on reality in practice. The juridical approach is used to analyze regulations that are related to the Notary Law, while the empirical approach is used to analyze the obligations of notaries in reading deeds which are seen as community behavior that has a pattern in community life that always interacts and relates to social aspects.The legal problem of reading deeds made by notaries, related to article 16 paragraph 7 of the Law on Notary Position regulates deviations from article 16 letter m. Where in Article 16 paragraph 7, it is stated that the reading of the deed is not mandatory, if the viewer wants the deed not to be read because the viewer has read it himself, knows and understands its contents, provided that it is stated in the cover of the deed and also on every minuta deed page initialed by the parties, and witnesses, as well as a notary. The legal consequence of the deed which is not read out by the notary based on Act No. 2 of 2014 concerning the Position of Notary Public, the deed which is not read out is still an authentic deed as long as the reasons for not reading the deed are stated.